PEMBERDAYAAN PEREMPUAN MELALUI MODEL LIFE SKILLS - Mastarina Barus (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT This paper aims to look at the activities of the empowerment of women have the same position, meaning that in every action there is no difference in the role and position that restricts women to take part in organizing and empowering communities, each running the social roles that are tailored to the circumstances and abilities, in order to further improve productivity, income and kemadiriannya. Efforts to empower women economically, especially look forward to the challenge requires high competitiveness, through a life skills program models. Relevance NFE give vocasional for these women to challenge the global economy is more emphasis on informal businesses, has been reduced and is constructed in the form of business activity Income Families. With the learning program is more focused solely on vocational skill , so that the graduates have the skills vocasional and non-vocational. This activity should be increased, empowered, synergized with activities in micro- economic empowerment, and be protected. In turn would be an alternative model of development of social economy. Kata Kunci : Pemberdayaan perempuan, model life skills.